DEVELOPING A FITRAH-BASED LEARNING MODEL IN ELEMENTARY SCHOOL - Dahuri Dahuri (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2023)
Human nature must always be developed through various learning activities so that a better person can be formed in accordance with his nature as a religious human being. Therefore, a comfortable and pleasant learning environment for students should always be created. Thus it will be easier for children to instill religious values ​​based on their nature so that it will be easy for them to follow the learning process at school. The purpose of this research is to describe the fitrah-based learning model at Elementary School, so the focus in this research are: (1) nature-based learning planning; (2) implementation of nature-based learning. Researchers, using a type of field research based on a qualitative approach. Data was collected using interviews, observation and documentation. The results of the research show that nature-based learning planning is carried out through extracurricular activities and fostering students' talents which are formulated in 6 models, namely: a) development of religious values ​​and moral ethics, b) physical and motor development of students c) m development of knowledge, d) grammar development programs, e) development of the soul socially and emotionally, and f) development of works of art. In practice, learning is done through grouping of students referring to the interests and talents of each student. This is important to do because the self-potential in children is growing rapidly due to the influence of demand and talent.